Faktor-Faktor yang Mempengaruhi Minat Masyarakat Menabung di Bank Syariah - Faqih Dwi Yoga; Atika Riasari (STIKes Ibnu Sina Ajibarang, 2025)
Indonesia is a country with the largest Muslim population in the world. However, public interest in Islamic banking services is still relatively low compared to conventional banking. The low interest is inseparable from various factors that influence individual decisions in choosing banking services. Interest itself can be understood as a person's tendency to be interested and pay attention to an object or activity voluntarily and accompanied by a sense of pleasure, which is formed through psychological and social processes. The type of research used in this study is field research, while the nature of this study is descriptive qualitative. The data sources used are primary data sources and secondary data sources. Data collection was carried out using two techniques, namely interviews and documentation. The data analysis technique used is by means of data collection, data reduction, data presentation, conclusions and verification. The results of the study showed that the most dominant factors influencing public interest are social and psychological factors. Social factors include the influence of family and the surrounding environment, which form habits and references in choosing banking services. Meanwhile, psychological factors include motivation to avoid usury practices and positive perceptions of the suitability of sharia principles applied in Islamic bank operations. Thus, efforts are needed to increase financial literacy, emotional approaches, and strengthening social relations to encourage the growth of public interest in Islamic banking services..